Technology as a Play Object in Teleanalysis with Young Children. Issue 1 (1st January 2021) - Sehon, Caroline
ABSTRACT: The COVID-19 pandemic, mid-March 2020, catapulted us into a new frontier of distance analysis and teletherapy as an emergency response to preserve continuity with both children and adults. The digital screen served as a metaphorical mask that protected the analytic couple from transmitting COVID-19 to one another, but patients and analysts alike were thrust into a shared catastrophic trauma. This paper will describe a four-times weekly, teleanalytic journey over the first six months of the COVID-19 pandemic with a seven-year-old child that built upon a three-year, in-office analysis. Rather than regarding teleanalysis as an experimental treatment, this paper illustrates ways children can employ technology as a play object, transference and countertransference can be analyzed online, and teleanalysis can be an effective and periodic alternative to in-office work with a vulnerable child population even after the end of the COVID-19 pandemic.